Randomized controlled trials design and implementation for community-based psychosocial interventions - Solomon, Phyllis L.; Cavanaugh, Mary M.; Draine, Jeffrey (New York ; Oxford : Oxford University Press, 2009)
From the initial stage of planning the RCT and developing its conceptual foundations through implementation, the authors provide a wealth of detail and case studies from social work practice research that assist readers to comprehend the detailed information provided.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Social service -- Research -- Methodology